Diagnosing diabetic foot osteomyelitis. (17th January 2020) - Senneville, Eric M.; Lipsky, Benjamin A.; van Asten, Suzanne A.V.; Peters, Edgar J.
Abstract: Bone involvement during an infection of the diabetic foot represents a serious complication associated with a high risk of amputation, prolonged antibiotic treatment and hospitalization. Diabetic foot osteomyelitis (DFOs) require a multidisciplinary approach given the usual complexity of these situations. DFO should be suspected in most cases especially in the most severe forms of soft tissue diabetic foot infections (DFIs) where the prevalence of bone infection may be up to 60%. Suspicion is based on clinical signs in particular a positive probe‐to‐bone (PTB) test, elevated inflammatory biomarkers especially erythrocyte sedimentation rate and abnormal imaging assessment using plain X‐ray as a first‐line choice. The combination of PTB test with plain X‐ray has proven effective in the diagnosis of DFO. The confirmation (definite) diagnosis of DFO is based on the results of a bone sample examination obtained by either surgical or percutaneous biopsy. Sophisticated imaging examinations such as Magnetic Resonance Imaging (MRI) and nuclear imaging techniques are useful where doubt persists after first‐line imaging assessment. These techniques may also help localize the bone infection site and increase the diagnostic performance of percutaneous bone biopsy. The quality of the microbiological documentation of DFO is likely to improve the adequacy of the antimicrobial therapy especially when medical (ie, no surgical resection of the infected bone tissues) is considered. The use of new (molecular) techniques for the identification of the bone pathogens have not yet proven superiority on classic cultural techniques for the management of such patients.